1989
DOI: 10.1002/ana.410250507
|View full text |Cite
|
Sign up to set email alerts
|

Simple and choice reaction time in patients with human immunodeficiency virus infection

Abstract: The performance of 56 homosexual men infected with human immunodeficiency virus (HIV) was compared to that of 23 HIV antibody-seronegative controls on simple (SRT) and choice (CRT) reaction time tasks. Patients were classified into 3 groups according to Centers for Disease Control clinical criteria. There were 18 patients who had acquired immunodeficiency syndrome (AIDS), 18 who had AIDS-related complex (ARC), and 20 who were HIV antibody-seropositive but otherwise asymptomatic (HIV-Ab+). The SRT task consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
2
1

Year Published

1989
1989
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 43 publications
2
17
2
1
Order By: Relevance
“…Simple RT and choice RT may measure different aspects, as indicated by Miller et al [7], who, by means of a factor analysis and using the long version of the CalCap, found that the three iterations of simple RT clustered as a single factor, and the six choice RT measures formed a separate factor. Similar to the results of other studies [1, 5], we did not find any differences between seropositives and controls on error scores, which indicates that, with regard to choice RT measures, patients may be slower in processing the information, but they have the same accuracy as controls in the response selection stage.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Simple RT and choice RT may measure different aspects, as indicated by Miller et al [7], who, by means of a factor analysis and using the long version of the CalCap, found that the three iterations of simple RT clustered as a single factor, and the six choice RT measures formed a separate factor. Similar to the results of other studies [1, 5], we did not find any differences between seropositives and controls on error scores, which indicates that, with regard to choice RT measures, patients may be slower in processing the information, but they have the same accuracy as controls in the response selection stage.…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies have found that AIDS patients perform worse than controls on computerized RT measures [1, 7]. Many studies have also found evidence of slower processing in asymptomatic seropositive individuals, which has been corroborated by psychophysiological studies.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Details of reports0samples included in the three meta-analyses SYMPTOMATIC HIV1 sample N CDC 87093 Treatment Ayers et al, 1987 Homosexual males 15 ARC NR Basso & Bornstein, 2000 Homosexual males 31 CDC B1-B2 21 on ART Bornstein et al, 1993 Homosexual or bisexual men 61 ARC NR Gibbs et al, 1990 Homosexual men 20 ARC 87 14 on AZT Grant et al, 1987 Homosexual men 13 ARC NR Heaton et al, 1995 Homosexual or bisexual men 86 CDC B 70.9 % on ART Jansen et al, 1989 Homosexual bisexual men 26 ARC 87 NR Krikorian and Wrobel, 1991 Homosexual bisexual men 18 ARC NR Martin et al, 1992 Male and female military personnel 15 Symptomatic NR Perdices & Cooper, 1989 Homosexual and bisexual men 18 ARC On AZT Perdices & Cooper, 1990 Homosexual Note. HIV 5 human immunodeficiency virus; CDC 5 Centers for Disease Control; NR 5 not reported; AIDS 5 acquired immunodeficiency syndrome; ARC 5 AIDS-related complex; ART 5 antiretroviral treatment; AZT, azidothymidine; ZDV 5 zidovudine; DDI 5 didanosine; DDC 5 dideoxycytidine; NVP 5 nevirapine; ADC 5 AIDS dementia complex; HAD 5 HIV-associated dementia; AAN 5 American Academy of Neurology.…”
mentioning
confidence: 99%